Electron Acceptor Availability Shapes Anaerobically Methane Oxidizing Archaea (ANME) Communities in South Georgia Sediments - Schnakenberg, Annika; Aromokeye, David A.; Kulkarni, Ajinkya; Maier, Lisa; Wunder, Lea C.; Richter-Heitmann, Tim; Pape, Thomas; Ristova, Petra Pop; Bühring, Solveig I.; Dohrmann, Ingrid; Bohrmann, Gerhard; Kasten, Sabine; et al. (Frontiers in Microbiology, 2021)
Anaerobic methane oxidizing archaea (ANME) are important for controlling atmospheric methane concentrations as they mediate anaerobic oxidation of methane (AOM) in marine sediments. However, the influence of electron acceptor (e.g., sulfate, iron oxides) availability on the ANME community composition in sediments remains to be elucidated. Here, we investigated the electron acceptor availability and compared the microbial in situ communities of three methane-rich locations offshore the Sub-Antarctic island South Georgia, by Illumina sequencing and qPCR of mcrA genes. Whereas MZ (MZ) sediments of Royal Trough and Church Trough comprised high sulfide concentrations (up to 4 mM and 19 mM, respectively), those of Cumberland Bay accounted for high concentrations of dissolved iron (up to 185 µM). Whereas the ANME community in the sulfidic sites Church Trough and Royal Trough mainly comprised members of the ANME-1 clade, the ANME-1-related clade are most abundant in the iron-rich site Cumberland Bay, indicating that the availability of electron acceptors has a strong selective effect on the ANME community. Therefore, this study shows that potential electron acceptors for methane oxidation may serve as environmental filters to select for the ANME community composition and adds to a better understanding of the global importance of AOM.